2021
DOI: 10.1136/bmjgh-2020-004377
|View full text |Cite
|
Sign up to set email alerts
|

Natural hazards, disasters and violence against women and girls: a global mixed-methods systematic review

Abstract: IntroductionDisasters triggered by climate and other natural hazards are increasing in frequency, severity and duration worldwide. Disasters disproportionately impact women and girls, with some evidence suggesting that violence against women and girls (VAWG) increases in disaster settings. Suggested risk factors for postdisaster VAWG include increased life stressors, failure of law enforcement, exposure to high-risk environments, exacerbation of existing gender inequalities and unequal social norms. We aim to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 58 publications
3
70
0
5
Order By: Relevance
“…Men and women are differentially affected by natural disasters: younger, less educated, and poorer women are the most affected group [14]. A recent systematic review also found that violence against women and girls increases in the aftermath of a natural disaster, compounding the effect of the disaster itself [15]. The repercussions of disasters on women can go beyond their own experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Men and women are differentially affected by natural disasters: younger, less educated, and poorer women are the most affected group [14]. A recent systematic review also found that violence against women and girls increases in the aftermath of a natural disaster, compounding the effect of the disaster itself [15]. The repercussions of disasters on women can go beyond their own experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The number of people affected by natural disasters has significantly increased, with women among the most vulnerable across a range of social and cultural contexts [ 4 ]. Vulnerability to natural disasters is rooted in structural challenges such as poverty, inequalities, rapid population growth, and the downstream risk of disasters such as displacement, lack of disaster management strategies, and resilience [ 4 , 5 ]. Recorded disaster fatalities indicate death rates of females are often much higher than that of males.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to death, the gendered impact of disasters includes higher rates of injuries, disability, chronic disease, mental illness, poverty, dependency, family conflict, and unemployment for females [ 7 , 8 , 9 ]. In addition to the vulnerabilities that women face as a consequence of natural disasters, they are also at risk of abuse and exploitation [ 5 ]. Because of these, women’s health is the prime concern usually violated as a result of disasters, particularly in low- and lower-middle-income countries [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, Thurston et al examined natural hazards, disasters, and violence against women and girls in a mixed-methods systematic review. 76 This review found that natural disasters—caused by climatological, geophysical, hydrological and meteorological hazards— were associated with violence against women and girls in diverse contexts. 76 While Thurston et al included climate change as a hazard, the other dimensions of sexual health beyond SGBV were not included, and their review was limited to women and girls.…”
Section: Introductionmentioning
confidence: 99%
“… 76 This review found that natural disasters—caused by climatological, geophysical, hydrological and meteorological hazards— were associated with violence against women and girls in diverse contexts. 76 While Thurston et al included climate change as a hazard, the other dimensions of sexual health beyond SGBV were not included, and their review was limited to women and girls. Second, Fatema et al published a systematic review protocol on women’s health-related vulnerabilities in natural disasters, which focused on physical and psychological health and sexual harassment.…”
Section: Introductionmentioning
confidence: 99%